Comparative analysis of mitochondrial and chloroplast genomes of Dracaena cambodiana from contrasting island habitats - Liang, Heng; Sun, Xiuxiu; Qi, Huasha; Chen, Jiali; Wang, Yidan; Wang, Chunmei; Liu, Moyang; Xia, Tengfei; Feng, Shiling; Chen, Cheng; Zheng, Daojun (Frontiers in Plant Science, 2025)
IntroductionDracaena cambodiana, a vulnerable species widely distributed in tropical and subtropical areas, has been recognized as a model plant for studying island conservation biology due to its fragmented habitat, slow growth, and ecological sensitivity. However, its organelle genome evolution and population divergence across different island environments remain poorly understood.MethodIn this study, we de novo assembled and annotated the complete chloroplast (cp) and mitochondrial (mt) genomes of two geographically distinct individuals of D. cambodiana from Hainan Island, China: a coastal area (SY) and a mountainous forest area (DF).ResultsBoth genomes showed conserved circular structures, but comparative analyses revealed key differences. The chloroplast genomes exhibited intergenic hotspot regions such as trnC-GCA–petN, trnL-UAA–trnF-GAA, and psaI–ycf4, which may serve as potential markers for taxonomy, population genetics, phylogeography and conservation biology of D. cambodiana. In the mitochondrial genomes, three genes (nad1, nad5, and rps11) showed the non-synonymous to synonymous substitution rate ratio (Ka/Ks) >1, indicating potential positive selection linked to environmental stress in the coastal population. Over 580 RNA editing sites were identified in each mitochondrial genome, with minor differences between DF and SY. These results suggest that while organelle genome structures are conserved, subtle molecular variations could potentially be associated with environmental differences between populations, although further investigation is needed to confirm adaptive significance.ConclusionThis study provides foundational genomic resources for understanding the adaptive evolution of D. cambodiana and supports conservation strategies in island ecosystems.